Wisata Halal Pengembangan Pariwisata Berbasis Nagari Menuju Wisata Halal Di Sumatera Barat - Dian Amelia; Ulfanora Ulfanora; Arya Putra Rizal Pratama (Nagari Law Review, 2022)
Minangkabau nature which has beauty, diversity of customs, the majority of which are Muslim, has beautiful nature, mountainous destinations and beautiful beaches, which are a halal tourist attraction in Indonesia in general, West Sumatra in particular. As the main destination for world tourists from other Islamic countries such as Malaysia, Dubai and others. Because West Sumatra is one of the halal tourist destinations, and the lowest government in West Sumatra is Nagari, it is interesting to study..This study uses a legal research method with an empirical/sociologicalapproach legal study(socio legal study) and normative (normative legal study ). The results of the study explain that the prospect of halal tourism that can be developed needs to be socialized to the City and Regency Governments and Nagari Nagari which have tourism potential. to be developed and managed by forming policy policies that are sourced from the Nagari Potential which will later give birth to policies that can contribute to Nagari PAD.